Correlation between Visfatin and Creatine Kinase Levels with Periodontal Health Status of Patients with Coronary Atherosclerosis and Chronic Periodontitis - Basma R. Omer; Maha Sh .Mahmood (College of Dentistry/ University of Baghdad, 2016)
Background: Visfatin is a novel adipokine that mainly secreted by visceral adipose tissue, had an important role in inflammation and immune system. Creatine Kinase (CK) which is an enzyme that is involved in energy metabolism, found in large amounts in myocardium, brain and skeletal tissues. This study is carried out To evaluate the periodontal health status of the study groups (chronic periodontitis and chronic periodontitis with coronary atherosclerosis) and control groups, to measure the salivary levels of visfatin and Creatine Kinase in these groups and compare between them, and to determine the correlations between salivary visfatin and Creatine Kinase levels with the periodontal parameters in the three groups. Materials and Methods: eighty participants, males and females were recruited in this study with age ranged from (30-60) years, they were divided into three groups: the first study group was the Chronic periodontitis group (n=30), the second study group was chronic periodontitis and coronary atherosclerosis (n=30) and the control group(n=20) which was healthy systemically with healthy periodontium. Periodontal health status was determined by measuring plaque index(PLI),gingival index (GI), probing pocket depth(PPD), bleeding on probing (BOP) and clinical attachment level (CAL),salivary samples were taken from each participants, salivary visfatin levels were determined by enzyme-linked immune-sorbent assay(ELISA) while the activity of salivary Creatine Kinase was determined spectrometrically by using the International Federation of the Clinical Chemistry (IFCC) method on Hitachi 911 Automatic analyzer. Results: The results of the study showed that the mean values of PLI, GI, visfatin, Creatine Kinase and the percentages of sites according to PPD scores, CAL scores, BOP were higher in the second study group with chronic periodontitis and coronary atherosclerosis than in the other groups with highly significant differences between the groups at (P≤0.01). Also by using Pearson Correlation Coefficient, salivary visfatin levels were correlated positively with all clinical periodontal parameters with a strong and positive correlation between salivary visfatin levels and CAL scores and PPD scores. Salivary Creatine Kinase levels were correlated positively with all clinical periodontal parameters with a strong and positive correlation between its levels and mean values of GI and percentages of BOP. Conclusion: The present study showed that salivary visfatin can be used as a marker for the development of coronary atherosclerosis and its levels are associated with the degree of periodontal destruction and showed that Creatine Kinase may be used as a marker for coronary atherosclerosis and chronic periodontitis.